Genetic diversity of Coffea canephora Pierre ex A. Froehner in Temanggung District, Indonesia based on molecular marker RAPD (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Authors. 2021. Genetic diversity of Coffea canephora Pierre ex A. Froehner in Temanggung District, Indonesia based on molecular marker RAPD. Biodiversitas 22: 4775-4783. Temanggung District in Central Java Province, Indonesia is one of robusta coffee production centers. The condition of coffee plantations in Temanggung shows variations in some morphological traits. Variations in coffee phenotypes are considered less profitable for farmers because they produce yields of undesirable quality in the global market. This study aimed to evaluate the genetic diversity of robusta coffee in Temanggung. The coffee plants were derived from six villages located at two levels of altitude. The morphological traits were observed from canopy width, trunk diameter, plant height, cherry volume, and bean volume, while the biochemical compositions were determined by caffeine content and brew’s pH value. The molecular assays were performed using PCR-RAPD with ten primers and species identification was based on the ITS rDNA. Our finding showed a variation in all morphological characters and biochemical compositions based on the LSD test 5%. The molecular marker RAPD revealed the genetic diversity by showing the DNA polymorphism levels of 95%, with the genetic similarity coefficient ranged from 0.35 to 0.86. The species identification also demonstrated that our robusta coffee was 97.11-99.70% similar to robusta coffee MK615737.1 from Philippines and robusta coffee DQ153593.1 from Cameroon. Thus, genetic diversity on six populations of robusta coffee was found, along with its variations on phenotypes which might lead the coffee yield quality to become uneven.
Keywords: Genetic diversity; molecular marker RAPD; robusta coffee